Ferrous metal waste, their safe and economical processing - O. M. D’jakonov (Литьë и металлургия, 2025)
The article provides a comparative analysis of existing approaches, opinions and proposals on environmentally safe and economically feasible methods of processing and recycling metalworking waste. The directions and achievements in processing steel and cast iron chips, ferroalloy screenings, grinding, rolling and filing sludge, scale, shot blasting waste, metal abrasive and aspiration dust are shown. For processing chips, the priority is remelting of low-oxidized chips in bulk in induction furnaces and hot briquetting; for oxide waste, the priority is reducing roasting and sintering in a mixture with an active reducing agent in endogas, followed by remelting of briquettes and sinters in furnaces of any type using traditional technology.